The Feasibility and User-Experience of a Digital Health Intervention Designed to Prevent Weight Gain in New Kidney Transplant Recipients—The ExeRTiOn2 Trial - Castle, Ellen M.; Dijk, Giulia; Asgari, Elham; Shah, Sapna; Phillips, Rachel; Greenwood, James; Bramham, Kate; Chilcot, Joseph; Greenwood, Sharlene A. (Frontiers in Nutrition, 2022)
Half of kidney transplant recipients (KTRs) gain more than 5% of their body weight in the first year following transplantation. KTRs have requested support with physical activity (PA) and weight gain prevention, but there is no routine care offered. There are few high-quality studies investigating the clinical value of diet, PA or combined interventions to prevent weight gain. The development and evaluation of theoretically informed complex-interventions to mitigate weight gain are warranted. The aims of this mixed-methods randomized controlled trial (RCT) were to explore the feasibility, acceptability and user-experience of a digital healthcare intervention (DHI) designed to prevent post-transplant weight gain, in preparation for a large multi-centre trial. New KTRs (< 3 months) with access to an internet compatible device were recruited from a London transplant center. The usual care (UC) group received standard dietary and PA advice. The intervention group (IG) received access to a 12-week DHI designed to prevent post-transplant weight gain. Primary feasibility outcomes included screening, recruitment, retention, adherence, safety and hospitalizations and engagement and experience with the DHI. Secondary outcomes (anthropometrics, bioimpedance, arterial stiffness, six-minute walk distance and questionnaires) were measured at baseline, 3- and 12-months. 38 KTRs were screened, of which 32 (84.2%) were eligible, and of those 20 (62.5%) consented, with 17 participants (85%) completing baseline assessment (Median 49 years, 58.8% male, Median 62 days post-transplant). Participants were randomised using a computer-generated list (n=9 IG, n=8 UC). Retention at 12-months was 13 (76.4%) (n=6 IG, n=7 UC). All a priori progression criteria were achieved. There were no associated adverse events. Reflexive thematic analysis revealed four themes regarding trial participation and experience whilst using the DHI. Halting recruitment due to COVID-19 resulted in the recruitment of 40% of the target sample size. Mixed-methods data provided important insights for future trial design. A definitive RCT is warranted and welcomed by KTRs. Trial registration (www.clinicalTrials.gov; no: NCT03996551).